2018
DOI: 10.17236/sat00165
|View full text |Cite
|
Sign up to set email alerts
|

Piscine mycobacteriosis – Involvement of bacterial species and reflection in pathology

Abstract: Piscine mycobacteriosis is a lethal disease with zoonotic potential, found worldwide in both fresh and marine fish. More than 20 strains of Mycobacterium spp. are known to persist in fish so far, but the pathogenicity is currently unknown for most of them. However, M. marinum is reported as one of the most pathogenic agents for fish and is involved in zoonotic cases. We examined 47 different cases from two zoological gardens, where fish tuberculosis was identified or previously suspected during the last ten ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…All four were isolated from freshwater systems, which suggests that these Mycobacterium strains specifically affect the freshwater stage of salmonid farming. First, macroscopically, the fish displayed biological characteristics consistent with previous descriptions of infections caused by members of the Mycobacterium genus (Aro et al 2014;Bruno et al 1998;Brocklebank et al 2003;Keller et al 2018;Luo et al 2018;Parikka et al 2012). Second, our bacteriological findings and 16S rRNA PCR results confirmed that the isolates belong to the Mycobacterium clade.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All four were isolated from freshwater systems, which suggests that these Mycobacterium strains specifically affect the freshwater stage of salmonid farming. First, macroscopically, the fish displayed biological characteristics consistent with previous descriptions of infections caused by members of the Mycobacterium genus (Aro et al 2014;Bruno et al 1998;Brocklebank et al 2003;Keller et al 2018;Luo et al 2018;Parikka et al 2012). Second, our bacteriological findings and 16S rRNA PCR results confirmed that the isolates belong to the Mycobacterium clade.…”
Section: Discussionsupporting
confidence: 89%
“…The typical gross pathology of mycobacteriosis in fish includes non-specific phenotypic changes, such as lethargy and anorexia, cutaneous ulcers, and decolouration (Bruno et al 1998;Brocklebank et al 2003;Luo et al 2018). Several case studies have identified the presence of multiple granulomas in the skin and internal organs (Bruno et al 1998;Brocklebank et al 2003;Luo et al 2018;Keller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over 150 species make up the genus Mycobacterium spp. and at least 20 species have been associated with fish, however, it is not always clear if species are the causative agent of mycobacteriosis as multiple species have been detected in diseased fish (Keller et al, 2018). As the primers used to test for Mycobacterium in the present study were genus specific and not speciesspecific, it cannot be determined if the fish were at risk of mycobacteriosis.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, a heavy mucus coating on the body surface, and a change in pigmentation as well as bleaching, have been reported and nonspecific external signs that are often very similar to that of other disease, including swollen abdomen, scale loss, ulcerative dermal necrosis ( Figure 1 ). External red lesions on the lateral line and shallow irregular ulcers have also been reported [ 1 , 47 , 48 , 49 ]. Moreover, abnormal behavior, including apathy, loss of appetite and the resulting emaciation can be observed, alongside exophthalmia, blindness, ascites and pale gills, as well as skeletal deformities such as spinal curvature or stunted growth [ 46 , 49 , 50 ].…”
Section: Course Of the Disease And Clinical Signsmentioning
confidence: 99%